2012
DOI: 10.4166/kjg.2012.59.5.372
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal Intussusception Due to Pedunculated Polypoid Gastrointestinal Stromal Tumor

Abstract: The gastrointestinal stromal tumor (GIST) is a mesenchymal tumor of the digestive tract showing differentiation along the line of interstitial cell of Cajal. The most GISTs in the stomach generally show the appearance of submucosal tumors. It is rare for GISTs to appear as a pedunculated polypoid lesion on endoscopy. We experienced a case of a 51-year-old man who had a pedunculated polypoid GIST. He was admitted to our hospital for nausea, vomiting, melena and severe anemia (hemoglobin 3.4 g/dL, hematocrit 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The treatment of gastroduodenal intussusception caused by gastric GIST mainly includes surgical resection and endoscopic treatment. Twenty-two previous cases 3 – 5 , 15 33 were treated by surgical resection and only two cases 11 , 14 were treated by endoscopic submucosal dissection (ESD). Notably, 12 cases underwent laparoscopic surgery, but no studies have reported the use of a robotic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of gastroduodenal intussusception caused by gastric GIST mainly includes surgical resection and endoscopic treatment. Twenty-two previous cases 3 – 5 , 15 33 were treated by surgical resection and only two cases 11 , 14 were treated by endoscopic submucosal dissection (ESD). Notably, 12 cases underwent laparoscopic surgery, but no studies have reported the use of a robotic approach.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 We identified 43 reported cases of gastroduodenal intussusception caused by gastric tumors in adults in the literature (PubMed), including 24 cases of gastric GIST. [3][4][5]11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The clinical characteristics of these previous cases and the current case are presented in Table 1. There were 9 men and 15 women, ranging from 23 to 95 years of age.…”
Section: Discussionmentioning
confidence: 99%